Strategi Pemasaran dalam Pengembangan Pelayanan Klinik Estetika - Daruki, Maria Wahyu; Suwedia, I Nyoman Gede Bayu Wiratama (UI Scholars Hub, 2020)
Aesthetic Services is growing in many big cities and developing cities in Indonesia. It is due to the tendency of people who want to improve their physical performance, in the era of national health insurance, private hospitals must also improve and add services to clients while maintaining good service and adding new services which can be another source of income for hospital. Services provided with mottto from Bhakti Rahayu Hospital Denpasar